EFECTOS DE LOS TRATAMIENTOS TERMICOS APLICADOS AL ACERO ASTM A182, SOBRE EL DESGASTE DESLIZANTE SECO, BAJO DISTINTAS CONDICIONES DE ENSAYO Y SU RELACION CON LA MICROESTRUCTURA - Avalos Collantes, Lander Isidro (2017)
The effect of the thermal treatments applied to the ASTM A182 steel, in relation to the dry sliding wear, was investigated under different test conditions: load and time. The purpose was to find the conditions to achieve the least wear. Fifty four (54) test specimens will be made for wear tests, according to ASTM D2782. Then, they were divided into three equal lots and the treatments were performed: quenching, annealing and normalizing. All samples were austenized at 1050 °C for 30 min. For quenching the cooling was in water. For the normalized, they were cooled in the air and for the annealing a slow cooling in the oven was done. All treatments were done in the Thermolyne muffle furnace. Hardness tests were performed on the IDENTEC digital durometer and the Rockwell C scale measurements. Wear tests were carried out on the MHASA Lathe by adapting the Amsler type device, using the ring-on-block configuration. The tests were run with three different load variations: 30N, 50N and 100N, at a constant speed of 250 rpm, and the test times were: 10', 20'30'40'50'60' (min). The wear measurements were made in μm. Microscopy was performed at the optical level using the ZEISS 1000X microscope.